FINLAND’S FOREIGN TRADE DURING THE POLYCRISIS - Roman M. Plyusnin (Научно-аналитический вестник Института Европы РАН)
The first years of the 21st century in Finland were marked by a series of challenging events. These included the coronavirus pandemic, an energy crisis, and a rupture in economic relations with Russia in 2022. Additionally, these events overlapped with internal economic challenges such as the aftermath of the eurozone crisis. This crisis for Finland resulted in significant increases in public debt and a negative trade balance, as well as difficulties for many large industries compared to similar industries in other European Union countries. The polycrisis had a particular impact on Finland’s foreign trade in goods, leading to gradual changes in its main trade partners and sectors. The purpose of this article is to consider these geographical shifts. And, if they are not yet so visible in the overall structure of foreign trade, with the possible exception of the actual cessation of trade with Russia, a decrease in the share of Germany and an increase in the role of the United States and China. These changes are more noticeable in industrial trade. For this reason, the geographical structure of trade in all major commodity groups was considered in the article. In the most knowledge-intensive industries, the importance of partners from the EU and other developed countries is declining, while the significance of countries from the Global South and Eastern Europe is growing. There is every reason to expect these trends to continue in the near future.